Pedagogy course self-study video - Graham, George; Beranich, Kathryn L. ([S.l.] : Human Kinetics, 1993)
Focuses on the teaching process - the skills and techniques that successful elementary physical education teachers use to make their classes more appropriate and beneficial for children
The companion video to the text Teaching children physical education : becoming a master teacher
Narrator: George Graham
Keywords: Physical education for children; Physical education and training; Teaching